Anklyosing Spondylitis Together with Familial Mediterranean Fever: A Concomitant Disease or a Feature of FMF? - Özlem Altındağ; Mehmet Karakoç; Neslihan Soran (Archives of Rheumatology, 2007)
Familial Mediterranean Fever (FMF) is an autosomal recessive disease characterized with self-limited recurrent episodes of fever and serositis. The association of FMF with ankylosing spondylitis (AS) was reported in previous studies as a rare condition and the mechanism of this association still remains unknown. The possible forms of joint involvement in FMF are acute or chronic mono-oligoarthritis and seronegative spondyloarthropathy. We described a case of FMF with AS in the case of a patient who had been diagnosed as having acute rheumatic fever (ARF) 20 years ago. We suggest that FMF with AS must be kept in mind in the presence of articular symptoms in patients with FMF. (Rheumatism 2007; 22: 110-13)